2005
DOI: 10.1109/jlt.2005.849883
|View full text |Cite
|
Sign up to set email alerts
|

Single-mode and polarization-independent silicon-on-insulator waveguides with small cross section

Abstract: Abstract-The fabrication restrictions that must be imposed on the geometry of optical waveguides to make them behave as single-mode devices are well known for relatively large waveguides, with shallow etch depth. However, the restrictions for small waveguides ( 1 m or less in cross section) are not well understood. Furthermore, it is usually a requirement that these waveguides are polarization independent, which further complicates the issues. This paper reports on the simulations of the conditions for both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…All SMCs for rib waveguides that have been formulated to date (Petermann 1976;Soref et al 1991;Powell 2002;Jinsong and Jinzhong 2004;Seong et al 2005;Xuejun et al 2009;Dorin and Ye 2013;Ziyang et al 2016), base on searching for such morphological parameters at which effective indices of higher order rib waveguide modes leak into the fundamental side-slab mode of corresponding polarization. They have one of the following forms: u < S(r) (Petermann 1976;Soref et al 1991;Jinsong and Jinzhong 2004), u < S(r,H) (Seong et al 2005;Xuejun et al 2009;Dorin and Ye 2013;Ziyang et al 2016) and u < S(r,H,t,w) (Powell 2002), where S is the criterion function. The function S in its most favorable form depends only on r, which is a dimensionless parameter.…”
Section: Single Mode Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…All SMCs for rib waveguides that have been formulated to date (Petermann 1976;Soref et al 1991;Powell 2002;Jinsong and Jinzhong 2004;Seong et al 2005;Xuejun et al 2009;Dorin and Ye 2013;Ziyang et al 2016), base on searching for such morphological parameters at which effective indices of higher order rib waveguide modes leak into the fundamental side-slab mode of corresponding polarization. They have one of the following forms: u < S(r) (Petermann 1976;Soref et al 1991;Jinsong and Jinzhong 2004), u < S(r,H) (Seong et al 2005;Xuejun et al 2009;Dorin and Ye 2013;Ziyang et al 2016) and u < S(r,H,t,w) (Powell 2002), where S is the criterion function. The function S in its most favorable form depends only on r, which is a dimensionless parameter.…”
Section: Single Mode Conditionmentioning
confidence: 99%
“…The function S in its most favorable form depends only on r, which is a dimensionless parameter. Up until now investigations aimed either directly at SMCs (Soref et al 1991;Hauffe et al 1999;Powell 2002;Lousteau et al 2004;Jinsong and Jinzhong 2004;Xuejun et al 2009) or focused on other properties of rib waveguides in the context of SMCs (Vivien et al 2002;Seong et al 2005;Milosevic and (3) Fig. 1 Schematic view of the investigated rib waveguide.…”
Section: Single Mode Conditionmentioning
confidence: 99%
“…It would be beneficial to capture the system error like a surface roughness; directionality of the side wall of the waveguide, etc, that will help us to understand some of the problems that might happen in the testing. Furthermore, it is usually a requirement that these waveguides are polarization independent, yet; there is a current trend in silicon photonic circuits to move to smaller device dimensions for improved cost efficiency and device performance which exacerbates polarization dependence issues [8] Conclusion A compact 90º optical hybrid has been designed and simulated on small size SOI waveguide technology (1.5 µm SOIbased rib waveguide, with 0.8µm rib waveguide). The fabrication restrictions that must be imposed on the geometry of optical waveguides to make them behave as single-mode devices are well known for relatively large waveguides, with shallow etch depth.…”
Section: Test Considerationsmentioning
confidence: 99%
“…The fabrication restrictions that must be imposed on the geometry of optical waveguides to make them behave as single-mode devices are well known for relatively large waveguides, with shallow etch depth. However, the restrictions for small waveguides are not well understood [8]. This paper provided a detailed procedure to design MMI based components with small dimensions.…”
Section: Test Considerationsmentioning
confidence: 99%
“…A waveguide can be of large cross section still having a single mode propagation through a cross sectional feature as shown in Fig. 2 birefringence conditions can be plotted on the same curve to determine the waveguide parameters that will make the waveguide to satisfy both these conditions simultaneously [128]. It is observed that for a single mode condition in a waveguide, quasi-TM mode condition plays the limiting condition.…”
Section: Rib Waveguidementioning
confidence: 99%